The Influence of Liquidity and Sales Growth on Capital Structure in Manufacturing Companies on The Indonesian Stock Exchange - Pratiwi Ar, Dhita; Nurfadilah, N.; Ramlah, R.; Lawalata, Izzac L.D; Panus, P. (Manunggal Halim Jaya, 2024)
This study aimed to determine the effect of liquidity and sales growth on capital structure. The research population is food and beverage manufacturing companies listed on the Indonesia Stock Exchange for 2017 - 2021. The research sample was six companies. Data was analyzed using linear regression and processed using the IBM SPSS 25 program. The results showed that the partial Current Ratio negatively and significantly affects the Equity Ratio. Meanwhile, sales growth has no significant impact on Debt-to-equity Ratios in food and beverage companies.